Numerical Analysis and Wind Tunnel Validation of Low-Temperature Ablators undergoing Shape Change. (October 2021) - Bianchi, Daniele; Migliorino, Mario Tindaro; Rotondi, Marco; Turchi, Alessandro
Highlights: Low-temperature ablators can be used for the design of re-entry capsule thermal protection systems. Camphor is preferred over naphthalene due to its thermophysical properties which prevent melting and maximize shape change. The validated numerical approach couples CFD analysis with model ablation and mesh evolution. The Phoebus capsule geometry is chosen as reference for the experimental test campaign through a numerical trade-off. Numerical rebuilding of experimental results with H-3 blow-down hypersonic wind tunnel conditions is satisfactory. Abstract: Ground testing of ablative materials aims at providing critical data on the material behavior under hypersonic reentry conditions. This is normally done in plasma wind tunnel facilities. However, non-negligible technical challenges are faced in order to duplicate the real flight conditions, such as inducing the recession of space-relevant ablative materials, which requires sufficiently high inflow total enthalpies, and/or reproducing the actual hypersonic flow velocity, which requires sufficiently high inflow Mach numbers. Often, ground facilities which are providing one requirement are lacking the other one and vice-versa. A possible solution is to use low-temperature ablators in continuous hypersonic blow-down tunnels, where aerodynamic and ablative tests with considerable shape change effects may be performed under reasonably low total temperature conditions and with affordable test durations. These substances are readily available, and they sublimate or ablate in a fashion that can be described fairly accurately by theory. This work has the objective to numerically characterize the shape change of such materials in hypersonic conditions, concurrently providing a validation against literature data and from a dedicated experimental ground test campaign. The numerical procedure relies on ad-hoc mesh generation/evolution strategies taking into account the material shape change, and is based on subsequent steady-state Computational Fluid Dynamics (CFD) computations coupled with a customizable gas-surface interaction wall boundary condition. Preliminary numerical simulations helped the design of the experiments to be carried out in the von Karman Institute (VKI) H-3 hypersonic wind tunnel, in particular for the identification of capsule geometry and size in order to maximize the shape change caused by ablation. Subsequently, camphor is identified as the most suitable low-temperature ablator to be used in the experimental campaign after a thorough analysis of its surface reaction thermodynamics and kinetics. Results from the CFD approach are first compared with a literature experimental test case and then with those of the previously designed experiments, featuring a camphor sub-scale capsule, underlying advantages and limits of the numerical procedure adopted. The obtained numerical and experimental results underline how it is possible to obtain a relevant shape change for relatively small exposure times by using low-temperature ablators in continuous hypersonic blow-down wind tunnels. Hence, results from this work can be used to support the design and sizing of the actual heat shield and the analysis of the capsule's aerodynamics and stability, accounting for shape change effects, by establishing an appropriate similitude between in-flight and on-ground conditions.